Harmonic reduction in power grids: implementing a four-legged multilevel inverter as an active power filter using model predictive control - Andang, Asep; Nursuwars, Firmansyah Maulana; Rahayu, Andri Ulus; Taufiqurrahman, Imam; Paryono, Ervan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This study explores the implementation of a five-level cascaded three-phase four-wire inverter as an active power filter to mitigate harmonics in power grids. Harmonic components in the load current are transformed and filtered to create a reference current, which serves as the foundation for designing the inverter’s switching pattern. The predicted current, generated through circuit modeling, is compared with the reference current using the model predictive control (MPC) method. The accuracy of this approach is evaluated using a cost function that measures the difference between the predicted and reference currents. Simulation results reveal that the application of the hybrid power filter can effectively suppress harmonics, reducing the total harmonic distortion (THD) to below 5%, thereby meeting power quality standards. Furthermore, it addresses load imbalances, ensuring that the phase currents at the source remain nearly equal. Additionally, the hybrid power filter significantly decreases the neutral current, reducing it to just one-tenth of its original value. While MPC has demonstrated its effectiveness in controlling power converters and multilevel inverters, its application to active power filters remains underexplored. This study investigates the potential of a four-legged multilevel inverter with MPC to enhance power quality by reducing harmonics in three-phase four wire systems.